2014
DOI: 10.1080/10495398.2014.882846
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNP inHSP90AB1and its Association with the Relative Thermotolerance and Milk Production Traits in Indian Dairy Cattle

Abstract: Heat shock proteins (Hsp) play crucial role in cellular thermotolerance and heat stress response. In the present work, Allele specific PCR (AS-PCR) was standardized to detect the nucleotide polymorphism within the HSP90AB1 gene (SNP g.4338T>C) in Indian breeds of dairy cattle. The identified genotypes were associated with relative thermotolerance in terms of physiological parameters and milk production traits. The results of the experiments revealed that the genotype frequency of CC, CT, and TT for Sahiwal wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
3
32
2
Order By: Relevance
“…The present study inferred that cows of genotype CT has the least rectal temperature and are able to maintain their body temperature under stress condition compared to other cows. In other studies, it was found that allele T at SNP locus T4338C was found to be associated with lower RT in Thai indigenous, Frieswal and Sahiwal cattle in India (Charoensook et al, 2012, Sajjanar et al, 2015. It is well described that RT of Bos taurus is higher than Bos indicus cattle and, as a result Bos taurus cattle are more sensitive to heat stress than Bos indicus (Mayengbam, 2008;Singh and Upadhyay, 2009).…”
Section: Association Of Hsp90ab1 Snp With Rectal Temperaturementioning
confidence: 93%
See 3 more Smart Citations
“…The present study inferred that cows of genotype CT has the least rectal temperature and are able to maintain their body temperature under stress condition compared to other cows. In other studies, it was found that allele T at SNP locus T4338C was found to be associated with lower RT in Thai indigenous, Frieswal and Sahiwal cattle in India (Charoensook et al, 2012, Sajjanar et al, 2015. It is well described that RT of Bos taurus is higher than Bos indicus cattle and, as a result Bos taurus cattle are more sensitive to heat stress than Bos indicus (Mayengbam, 2008;Singh and Upadhyay, 2009).…”
Section: Association Of Hsp90ab1 Snp With Rectal Temperaturementioning
confidence: 93%
“…The present study inferred that Karan Fries cows of genotype AA recorded least respiration rate per minute and is better thermo-tolerant under stress condition than other cows. Previous studies reported that allele T at SNP locus T4338C was associated with lower RR in Thai indigenous, Sahiwal and Frieswal cattle in India (Charoensook et al, 2012;Sajjanar et al, 2015). Increased respiration is an important thermoregulatory response to heat stress.…”
Section: Association Of Hsp90ab1 Snp With Respiration Ratementioning
confidence: 97%
See 2 more Smart Citations
“…Effects of the SNP g.1524G>A, g.3494T>C and g.6601G>A within HSP70A1A affect thermo-tolerance in Chinese Holstein cattle . In contrast allele T at SNP g.4338>C of HSP90AB1 gene was found to be associated with heat tolerance coefficient in Thai native cattle (Charoensook et al, 2013), Sahiwal and Frieswal cattle in India (Deb et al, 2013;Sajjanar et al, 2015). Recently in Jersey crossbred cows found that of CC genotype had better thermo-tolerance capacity at (T17872112C) locus of HSP90AB1 gene .…”
Section: Pcr Primers and Amplificationsmentioning
confidence: 95%